Evaluation of Soybean [Glycine Max (L.) Merrill] Germplasm at Multi-Environments of Nepal and Their Stability Assessment using AMMI and GGE Biplot Analysis - Ghimire, Netra Hari; Dhakal, Krishna Hari; Pandey, Madhav Prasad; Joshi, Bal Krishna (Journal of Nepal Agricultural Research Council, 2024)
A total of 150 soybean germplasms received from various sources were evaluated in a field study at DoAR, Dasharathpur; Surkhet, GLRP, Rampur, Chitwan, and NARC, Khumaltar, Lalitpur during the consecutive years of 2019 and 2020. The study employed an alfa lattice design with three replications to assess diversity, agronomic performance, and the selection of stable, early maturing, and high yielding genotypes from the inner terai to mid hills of Nepal released variety Puja and Tarkari Bhatmas-1 served as standard check. Major quantitative traits like days to flowering, days to maturity, plant height, number of primary branches per plant, number of nodes per plant, number of pods per plants, grain yield, biomass, harvest index and seed weight were recorded. A pooled mean analysis of variance revealed that all recorded traits were found significant difference for genotypic, environmental and genotypic by environmental effect at (p<0.00). The results revealed that the following genotypes: 200525(Rampur) (2074.9 kg/ha), NGRC06833 (2074.3 kg/ha), NGRC06835 (2041 kg/ha) and (TGX1987-62F (1988.3 kg/ha) were the highest yielders and ideal genotypes in GGE biplot analysis genotypes 2003KS-KBxTB1-2.1-3 (103 days), NGRC06826 (105 days), 2003KS-TB1xKB-5.34 (105 days) were noted for their early maturity. GGE biplot revealed sufficient diversity among the genotypes. Genotype NGRC06811 lies near the equality line for Surkhet, indicating superior performance in that environment. Conversely 200525 Rampur and NGRC06835 performed better at Rampur, while Seti, Sathiya excelled at Khumaltar. Notably NGRC08243 and Baglung black were poor performers across all three locations concerning the trait grain yield. Among the genotypes Soy Agd-005, NGRC02679, Tarkari Bhatmas 1, Bringi, Pyuthan Bazar-2016, AGS 371 were identified as the most stable whereas NGRC06811, NGRC02716, NGRC06821, Seti, NGRC06832 exhibited significant instability and were the largest contributor to genotype by environment interaction. This study provides valuable insights that can be utilized for future crop improvement efforts in Nepal by leveraging these germplasms.